Granulocytic Sarcoma by AML M4eo (inv16) after Allogeneic Stem Cell Transplantation without Bone Marrow Involvement - Stephan Zaenker; Stefan Schweyer; Justin Hasenkamp; Lorenz Truemper; Gerald Wulf (Case Reports in Hematology)
Granulocytic sarcoma (GS) represents a rare type of extramedullar manifestation from the acute myeloid leukaemia (AML). We report the case of a patient with recurrences of AML M4eo leukaemia in the uterus and the small intestine at 3 and 5 years, respectively, after matched related peripheral blood stem cell transplantation (PBSCT). The patient underwent the withdrawal of immunosuppression, hysterectomy, and local irradiation at first relapse, as well as systemic chemotherapy and donor lymphocyte infusions at second recurrence, inducing a second and third complete remission, respectively. At year six after transplantation, the patient experienced disease progression by meningeosis leukaemia to which she succumbed despite intrathecal chemotherapy. Following allogeneic stem cell transplantation, awareness for atypical manifestations of granulocytic sarcoma appears prudent, the cellular immunotherapy should aim at immunological disease control.